Rancang Bangun Aplikasi Absensi Siswa (Studi Kasus Lkp Karya Prima Kursus) - Muhammad Zen; Supiyandi Supiyandi; Chairul Rizal; Muhammad Eka (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2021)
AbstractAttendance activities are very important activities and should not be forgotten in every teaching and learning process carried out. Current attendance at the Karya Prima Course LKP still uses a manual system so that the attendance file is very large and difficult to find, especially if the student takes a long leave. The application developed is expected to help make attendance easier as well as attendance reports related to teacher salaries. Keywords : Student Attendance, Web Application